Upaya Meningkatkan Hasil Kebugaran Jasmani Siswa Kelas IX-F SMP Negeri 30 Semarang Menggunakan Metode Pembelajaran Ular Tangga (psnppg, 2025)
This research was motivated by the lack of knowledge about physical fitness activities and the low enthusiasm of Grade IX-F students in Physical Education (PE) classes at SMP Negeri 30 Semarang. The aim of this study was to examine the improvement in PE learning outcomes among ninth-grade junior high school students using a snake and ladder game-based learning model. This study employed a Classroom Action Research (CAR) method conducted in two cycles. The subjects of the study were 32 ninth-grade students. In the first cycle, the average class score was 77.2, with 25 students reaching the minimum mastery criteria (KKTP) and 7 students not yet achieving it, resulting in a mastery percentage of 78.1%. In the second cycle, there was an improvement in learning outcomes with an average class score of 87.2; 30 students achieved the KKTP and only 2 did not, resulting in a mastery percentage of 93.8%. These results indicate that the implementation of the snake and ladder game-based learning model can be used to improve students' learning outcomes.
Keywords: Physical Fitness; Learning; Snake and ladder game